Synthesis and photophysical properties of novel pyrene–metalloporphyrin dendritic systems. Issue 28 (24th May 2019) - Rojas-Montoya, Sandra M.; Vonlanthen, Mireille; Porcu, Pasquale; Flores-Rojas, Gabriel; Ruiu, Andrea; Morales-Morales, David; Rivera, Ernesto
Abstract : Energy transfer studies were performed on a series of new pyrene–metalloporphyrin (Zn, Cu, Mg and Mn) dendritic constructs. Abstract : A novel series of dendronized porphyrins bearing pyrene units in the periphery (Porph- O -G n ) and their metal complexes (M-[Porph- O -G n ]) are reported. The pyrene-containing Frechet-type dendrons up to the first generation were synthesized and further reacted with 5-phenol-10, 15, 20-triphenylporphyrin via an esterification reaction to afford the desired pyrene-labeled dendronized porphyrins. Later, these compounds were used as ligands to produce the corresponding complexes of Zn 2+, Cu 2+, Mg 2+ and Mn 3+ . With the compounds in hand, the optical and photophysical properties of the dendritic metalloporphyrins were studied by absorption and fluorescence spectroscopy. The quantum yields, Förster radius and efficiency of energy transfer were determined and discussed as a function of the structure and the donor–acceptor distances, finding an efficient energy transfer from the pyrene moiety to the metallated porphyrin core in each case.